AB0658 ROLE OF NAILFOLD CAPILLAROSCOPY IN MONITORING LUNG INVOLVEMENT OF SYSTEMIC SCLEROSIS. (June 2019) - Groseanu, Laura; Paraschiva, Patricia; Balanescu, Andra; Bojinca, Violeta; Opris-Belinski, Daniela; Berghea, Florian; Mazilu, Diana; Daia-Iliescu, Sanziana; Saulescu, Ioana; Borangiu, Andreea; Cobilinschi, Claudia; Negru, Maria Magdalena; et al.
Abstract : Background: The usefulness of capillaroscopy in the follow-up of scleroderma (SSc) patients and the possible prognostic role for the appearance of visceral involvement is suggested by many authors but still under debate. Objectives: The aim of this study was to assess the role of monitoring capillaroscopic abnormalities (qualitative and semiquantitative) in relation with parameters of interstitial lung involvement and pulmonary arterial hypertension(PAH). Methods: Longitudinal prospective study, 118 SSc patients, follow-up 2000-2017 based on MEDS evaluation sheets. Student t-test/Mann-Whitney test, chi-square test were used to evaluate differences across subgroups. Pearson's bivariate correlation/Spearman's rank correlation coefficient were used to evaluate the association between variables. Nailfold videocapillaroscopy (NVC) was performed by a trained physician: qualitative (scleroderma pattern) and semiquantitative scoring (microangiopathy evolution score-MES) were evaluated. Results: 118 patients were included, 103 females (87, 29%), 50, 58(12, 71) years old at diagnosis, 53.39% diffuse subset, mean disease duration 2, 81(4.3) years, mean follow-up duration 4.42(3.16)years. At baseline 43.22% of the patients had lung fibrosis, 18.64% had PAH, 9, 32% had both. At first capillaroscopic evaluation: 12.7% had early, 46.61% active and 37.29% late pattern, medium MES was 4, 76(1.43). Baseline active and late capillaroscopic pattern were correlated with lung fibrosis (χ2=9.62, p=0.047) and PAH (χ2=15, 36, p=0.004). A strong correlation was identified between initial MES and FVC (r=-.47, p=0.002), FEV(r=-.45, p=0.003), DLCO (r=-.51, p< 0.001) and sPAP (r=0.34, p<0.001). At the 2nd evaluation 5.93% of the patients had early, 0.85% active and 54, 24% late scleroderma pattern, mean MES was 5.88(1.74). 19.49% had one step progression of capillaroscopic pattern, 1.69% had 2 steps progression. Lung involvement worsening was defined as decrease of FVC >15%, DLCO>10%, new diagnosis of alveolitis on high resolution computerized tomography or new diagnosis of PAH. Active and late capillaroscopic pattern were correlated with diagnosis of lung fibrosis (χ2=14, p=0.007) and pulmonary hypertension at follow-up examinations (χ2=14, 2, p=0.007). Progression of capillaroscopic pattern at follow-up evaluations was not correlated with significant worsening of lung volumes, DLCO, sPAP. Instead, progression of MES (>1) was asociated with worsening of FVC (r=0.32, p<0.001), FEV(r=0.18, p=0.04), DLCO(r=0.21, p=0.02) and new diagnosis of lung fibrosis on HRCT (r=0, 19, p=0.035). Conclusion: Active and late capillaroscopic pattern are associated with increased frequency of interstitial lung disease and pulmonary hypertension in SSc patients. Semiquantitative scoring (microangiopathy evolution score), rather then qualitative capillaroscopic assessment can have a predictive role for new involvement or worsening of previous lung involvement (especially interstitial lung disease) in scleroderma patients, confirming the putative role of capillaroscopy as biomarker in SSc. References: [1] Sulli a How to Score the Qualitative Capillaroscopic Patterns in Systemic Sclerosis annals of the Rheumatic Diseases 2013;72:A11 Disclosure of interests: Laura Groseanu: None declared, Patricia Paraschiva: None declared, andra Balanescu Speakers bureau: multiple, Violeta Bojinca Speakers bureau: multiple, Daniela Opris-Belinski Grant/research support from: GLORIA, Speakers bureau: multiple, Florian Berghea: None declared, Diana Mazilu Speakers bureau: Pfizer, UCB, Sanziana Daia-Iliescu: None declared, Ioana Saulescu: None declared, andreea Borangiu: None declared, CLAUDIA COBILINSCHI: None declared, Maria Magdalena Negru: None declared, cosmin-laurentiu constantinescu: None declared, Violeta Vlad: None declared, Mihai abobului: None declared, Ruxandra Ionescu: None declared